Analisis Tingkat Koneksi Politik Terhadap Tax Avoidance: Perusahaan Manufaktur di BEI Tahun 2015-2019 - Kurnia Imanuella; Theresia Woro Damayanti (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2022)
Taking into consideration that the highest national income source came from the tax revenue but cannot be neglected, that tax avoidance is one of the determining factors why its operation has not been performed well. Political connections presumed to be one driver of the tax avoidance popularity. This study aimed to investigate the effect of corporate political connection towards tax avoidance. The analysis has used secondary data of manufacturing companies financial statements listed in Indonesia Stock Exchange over the period of 2015-2019. 376 qualified financial statements were processed by using panel data regression analysis through eviews. The result indicates there is a significant association between political connections and tax avoidance behaviour.